ЗАДАЧА С КОНОРМАЛЬНОЙ ПРОИЗВОДНОЙ ДЛЯ УРАВНЕНИЯ ЭЛЛИПТИЧЕСКОГО ТИПА С ОДНОЙ ЛИНИЕЙ ВЫРОЖДЕНИЯ - Исламов, Х. (SCIENCE and SOCIETY, 2022)
The given article proves uniqueness of the theorem and existence of the solution conormal derivatives for the types of elliptic education with broken lines.